Comparative monogenetic infections of some fish species in Greater and Lesser Zab rivers, Kurdistan Region, Iraq. - Samir Jawdat Bilal; Maysoon Omar Nasraddin (Zanco Journal of Pure and Applied Sciences)
A total of 953 fish specimens (521 females and 432 males), belonging to 19 species were collected from Greater Zab river at Aski-Kalak town and from Lesser Zab river at Kanibi village, Taqtaq town in north of Iraq, during the period of January to December 2022. only 11 fish species (842 specimens) were sympatric in both rivers, 2 species (14 specimens) were in Greater Zab and 6 species (97 specimens) were in Lesser Zab. The samples were examined for ecto-parasites. The study revealed the existence of 31 monogenean species, including twenty-one species of Dactylogyrus, three `species of Dogielius, two species of Diplozoon and one species of Solostaminides.  During present study, it was found that, overall the prevalence of monogenean infection was 59.44 % for grater Zab river and 54.6% for the lesser Zab river. There were no significant differences in the percentage incidence in the overall of infection with this group of parasites from both rivers instead of there was obvious difference in the distribution and spread of parasitic fauna in both rivers.